Os gigantes e as multidões : estádios e cultura expositiva em Belo Horizonte (1950-1965) - André Maia Schetino (2014)
The sport can be considered one of the most striking phenomena of our time. Since its emergence as a modern practice, its modalities, as well as the values, take cities and transform their dynamic. The sporting spectacle constituted a great consumer market, since that involves the so-called "mega sporting events" - such as the FIFA World Cup and the Olympics - even the leisure practices of urban dwellers. Therefore, this study aims to investigate the relationship between sports culture and urban culture in Belo Horizonte, and in this context, the construction of the Independendência (1950) and Mineirão (1965) stadiums. For that, we’ve researched a number of aspects of the city of Belo Horizonte and of sport. Initially, we dedicate ourselves to a brief overview of the city of Belo Horizonte, bringing some notes on its opening and early years. Then, we focus in the period between 1950 and 1965, the focus of this study. Subsequently we present an investigation of the sports culture and urban culture. We show how the development of sports in Belo Horizonte transforms the customs and way of life of its inhabitants, making a lifestyle guided by the values of sport phenomenon arise. After that, we dedicated to the stadiums: its construction and inauguration, turning them into privileged spaces of the manifestation of sporting culture. At this moment we highlight some policy issues surrounding the context of its construction, and also approached other points: the discourse on science and technology involved in its construction, its relationship with the city space and the heavy industrialization from the idea of the great constructions and buildings. Yet from the perspective of the stadiums, we also seek to give voice to the people, the workers who participated in the construction of stadiums, athletes who were enshrined in those spaces and crowds of fans who flocked to these concrete giants. In this sense, we also highlight two great moments of these stadiums: the World Cup Soccer 1950 - to mark the inauguration of the Independência stadium - and the games and festivities for the inauguration of Mineirão stadium, in 1965. We were able to see how the construction of stadiums is constituted a important mark not only in buildings, but also as important for the expression of the sporting culture of the Belo Horizonte citizen.